Unseen Battles: Pre-Treatment Anxiety Among Patients with Thyroid Carcinoma (Bangladesh Journal of Nuclear Medicine, 2026)
Background: When diagnosed with cancer, patients often experience significant psychological stress and fear of death. Thyroid carcinoma, although more treatable, carries similar stigma, leading to acute mental stress for those affected. Patients scheduled for therapy frequently endure considerable pre-treatment anxiety about prognosis and treatment outcomes. This study aims to assess anxiety disorders in thyroid carcinoma patients before they undergo radioiodine therapy. Materials and Methods: This observational study was conducted at the Institute of Nuclear Medicine and Allied Sciences-INMAS, Mitford between January 2024 and June 2025 on 150 patients referred for radioiodine therapy (M= 56, F= 94). Participants received doses of 100 mCi, 150 mCi, or 200 mCi based on clinical indications. Anxiety levels were evaluated using the Generalized Anxiety Disorder-7 (GAD-7) scale, with data analyzed using SPSS and significance determined via Chi-square test. Results: The 64 patients receiving radioiodine therapy indicated varying levels of anxiety: 76.6% at 100 mCi showed minimal anxiety, while 17.2% had mild anxiety, 4.7% moderate, and 1.6% severe. For those at 150 mCi, 74.2% had minimal anxiety, 14.5% mild, 8.1% moderate, and 3.2% marked anxiety. Among 24 patients receiving 200 mCi, 62.5% exhibited minimal anxiety, 16.7% mild, 8.3% moderate, and 12.5% severe. Chi-square test results were insignificant (P > 0.05). Conclusion: Pre-treatment anxiety is common in thyroid carcinoma patients, regardless of gender. It underscores the necessity of regular psychological evaluations and psychosocial support prior to radioiodine therapy, suggesting that addressing mental health alongside physical treatment can enhance patient outcomes and quality of life.Bangladesh J. Nuclear Med. 28(2): 298-302, July 2025